A Review on Biomaterials in Dentistry: Innovations and Applications (The Review of Diabetic Studies, 2024)
In recent years, there has been significant progress in the field of biomaterials, particularly in their application within dentistry. This review critically examines the current innovations and applications of biomaterials in dental practice, utilizing secondary data as the primary source of information. The study explores the advancements in material science that have led to the development of new composites, ceramics, polymers, and bioactive materials designed to improve the efficacy, durability, and aesthetic qualities of dental restorations and prosthetics. Emphasis is placed on the integration of nanotechnology, tissue engineering, and regenerative medicine, which have revolutionized traditional approaches and led to the development of biomaterials with enhanced biocompatibility and functionality. The review also addresses the challenges and limitations associated with existing dental biomaterials, along with future research directions aimed at overcoming these obstacles. By synthesizing data from a wide array of studies, this review provides a comprehensive overview of how innovations in biomaterial technologies are shaping the future of dentistry and improving patient outcomes.